The Test Based on Meta-Analysis on “Does Workaholism Prefer Task Performance or Contextual Performance?” - Cheng, Bang; Gu, Jiajun (Frontiers in Psychology, 2022)
The relationship between Workaholism and Work Performance is explored by Meta-analysis in this article. After searching relevant references, we had gained 94 individual effect sizes (n=57352), 45 individual samples, 37 references. Through the heterogeneity test, it shows that the random effect model is more suitable. The main effect analysis shows that there is a significant positive correlation between Workaholism, working excessively, working compulsively and Work Performance, and further analysis shows that Workaholism emphasizes on the improvement of Contextual Performance. The sub-group test shows that the relationship between Workaholism, working excessively, working compulsively and Work Performance are influenced by the measurement tools of Workaholism, but not influenced by cultural background differences and time-lag research. The above results show that Workaholism and its dimensions have different influences on different aspects of Work Performance. Besides, it’s worthy to consider the moderating function of measurement tools of Workaholism in the relationship between Workaholism and Work Performance.